2016
DOI: 10.1117/1.jbo.21.1.015005
|View full text |Cite
|
Sign up to set email alerts
|

Nonequispaced grid sampling in photoacoustics with a nonuniform fast Fourier transform

Abstract: To obtain the initial pressure from the collected data on a planar sensor arrangement in photoacoustic tomography, there exists an exact analytic frequency-domain reconstruction formula. An efficient realization of this formula needs to cope with the evaluation of the data's Fourier transform on a nonequispaced mesh. We use the nonuniform fast Fourier transform to handle this issue and show its feasibility in three-dimensional experiments with real and synthetic data. This is done in comparison to the standard… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The algorithm exploits the fast computational speed of FFT to reconstruct B-scans in fractions of a second to afford 3D images immediately after acquisition. Reconstruction speeds have been previously accelerated using standard frequency domain reconstruction with experimental optoacoustic data, with a 53 s-reconstruction time for a data size of 200 x 200 x 100 voxels in Fourier domain, compared to nearly 3 hours in time-domain based reconstruction for the same data set 27 , representing a 200-fold faster reconstruction. Recently, Fourier reconstruction times of 0.25 s were reported for B scans with 600 x 751 pixels 44 and of 0.7 s for multi-layer volumetric reconstruction of a 40 x 40 x 2000 voxel-data set 45 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The algorithm exploits the fast computational speed of FFT to reconstruct B-scans in fractions of a second to afford 3D images immediately after acquisition. Reconstruction speeds have been previously accelerated using standard frequency domain reconstruction with experimental optoacoustic data, with a 53 s-reconstruction time for a data size of 200 x 200 x 100 voxels in Fourier domain, compared to nearly 3 hours in time-domain based reconstruction for the same data set 27 , representing a 200-fold faster reconstruction. Recently, Fourier reconstruction times of 0.25 s were reported for B scans with 600 x 751 pixels 44 and of 0.7 s for multi-layer volumetric reconstruction of a 40 x 40 x 2000 voxel-data set 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Numerical errors during the interpolation step have been reduced by employing a Sinc interpolation function, yet this remains computationally expensive 53 . Alternatively, non-equispaced grid sampling has been implemented to avoid the interpolation step in Fourier domain 27 ; however, this results in a significant increase in computational complexity. In this work, we used a cubic spline interpolation as a compromise between quality and computational cost.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimal choice for PAT applications is yet to be determined. For instance, [66] has shown that a non-uniform distribution of the sampling locations in single-point sub-sampling can be used to focus into a specific area (at the expense of the resolution elsewhere). A theoretical examination, e.g., through micro-local analysis [67], could help to gain new insights on this.…”
Section: Discussionmentioning
confidence: 99%
“…It used in a wide range of applications, such as image filtering, image analysis, image reconstruction, and image compression. In the literature, several papers have described methods for approximating one-dimensional Non uniform Fast Fourier Transforms by interpolating an oversampled Fast Fourier transforms, start with [17] and including [18], [19], [20], [21], [22], [23], [24], [25], [26], [27]. In [28] the fundamentals of Fourier transform, Fourier series, discrete Fourier transform and fast Fourier transform with simple examples and review of Fourier transform to supply a clear understanding of its applications in power quality issues.…”
Section: Related Workmentioning
confidence: 99%